Basic Properties of fly Ash/Slag -Concrete Slurry Waste Geopolymer Activated by Sodium Carbonate and Different Silicon Sources - Gao, Yingli; Duan, Kairui; Xiang, Shuncheng; Zeng, Wei (Frontiers in Materials, 2021)
Abstract: As a kind of granular waste with complex composition and alkali corrosiveness, concrete slurry waste (CSW) has severe recycling limitations in the Ordinary Portland cement (OPC). Considering this, a new type of geopolymer, prepared by granulated blast furnace slag/fly ash, concrete slurry waste, and powdered activators (sodium carbonate and different silicon sources including sodium metasilicate pentahydrate and silica fume), was adopted to conduct a comparative study with the OPC counterpart. In this study, the homogenized CSW was mixed in the OPC and geopolymer with a constant ratio of 50 wt%, respectively. Then the properties were studied in terms of the flowability, setting times, mechanical strengths, and microstructures. The results showed that better flowability (200mm) could be achieved in the obtained geopolymer than in the OPC reference group (95mm) by increasing the powdered activators. The setting time of the OPC was significantly shortened due to the addition of CSW. The strengths of geopolymer were supported by the produced C-A-S-H and carbonates, with less chemically bonded water than the hydration products in the reference group. The dominant size of pores in the hardened geopolymer was much smaller than that in the OPC group which was 80nm. Silica fume could be the alternate of the sodium metasilicate pentahydrate and had an insignificant negative impact on the fresh and hardened properties and microstructures of the geopolymer when the incorporation rate was within 5%.